Sedimentology and Stratigraphy of the Upper Devonian Imperial Formation, Mackenzie Valley, Northwest Territories, Canada - Acker, Rachael (Graduate Studies, 2013)
A well exposed outcrop of the Upper Devonian Imperial Formation at the Imperial River type section, Northwest Territories, is described and analyzed in detail to evaluate depositional and sequence stratigraphic models. The formation is divided into lower, middle and upper intervals, with the present study focusing on the sandstone‐rich middle interval deposits. Eight facies are described and three facies associations interpreted within the middle interval, which comprise forty upwards‐ coarsening packages (3 – 20 m thick) at Imperial River. Each upwardscoarsening package is considered a parasequence, which records the shift from distal to proximal shelf and shoreface deposits. Analysis of various regional successions of parasequence stacking patterns, through integration of seismic data, well logs and outcrop data, is used to refine sediment distribution predictions and develop a revised stratigraphic framework for the Imperial Formation. The development of regional and local depositional models, should provide an initial framework for hydrocarbon exploration in the Imperial Formation of the Mackenzie Corridor.